Spatial symmetric multi-level coding absolute phase retrieval for color 3D real-time measurement - Li, Yaqi; Cao, Yiping; Ran, Longyi (Measurement : journal of the International Measurement Confederation, 2026)
•A symmetric multi-level coding based temporal phase unwrapping is proposed.•Only one auxiliary coding pattern is used for 3D color real-time measurement.•Proposed temporal phase unwrapping method can enhance robustness, fault tolerance and reconstruction accuracy.•Proposed new projection strategy boosts reconstruction rate from 1/4 to 3/6. A spatial symmetric multi-level coding based absolute phase retrieval is proposed, which can minimize the number of coding patterns to only one with high robust for color real-time 3D measurement, thus has better real-time performance. Compared with the traditional spatial coding, the proposed coding method is able to directly solve the fringe order information despite the presence of more residuals in the wrapped phase, and then deduce the level of each bit of code-word. In addition, symmetric coding can interact with the left and right regions to prevent fringe order recognition errors, which shows a higher fault tolerance. The HSI multi-level Gray code demodulation temporal phase unwrapping is used to suppress the error caused by different chroma, thus the reconstruction has strong robustness against color interference. Meanwhile, in order to improve the efficiency of real-time measurement, a projection strategy of five frames of phase-shifting pattern plus one frame of shared symmetric multi-level coding pattern is proposed in which any frame of wrapped phase can be solved with corresponding three adjacent frames of five frames of phase-shifting deformed patterns, which improves the reconstruction rate from traditional one reconstruction in four projected patterns to three reconstructions in six projected patterns. Experimental results show the effectiveness of the proposed spatial symmetric multi-level coding method and projection strategy. It plays a great prospect in color real-time 3D measurement.